Uzbek Wedding Ceremony Concept (Texas Journal of Philology, Culture and History, 2024)
The wedding is one of the most important ceremonies for the Uzbek people. The wedding ceremony has been refined and enriched over the centuries and includes various customs and traditions. This article discusses the types of Uzbek wedding ceremonies and their meanings